From science to practice: The AGSUS protocol for monitoring and certification of sustainable soil management and carbon sequestration - Noellemeyer, Elke; Álvarez, Lucila; Alvarez, Cristian; Dillchneider Loza, Alexandra; Farrell, Mauricio Aníbal; Fernandez, Romina; Frank Buss, Elisa; Frasier, Ileana; Gaggioli, Carolina; Gili, Adriana; Gómez, Flarencia; Lara, Gabriel; et al. (Elsevier, 2024)
Sustainable soil management is indispensable for achieving the UN Sustainable Development goals and soil carbon sequestration for climate change mitigation has gained importance in recent years, yet there are few examples of projects carried out to this purpose, and protocols that facilitate this task. Here we present a monitoring system that relies on sampling soils in the field, as opposed to a modeling approach. The high spatial variability of SOC was addressed by requiring that the participating farms divide their land according to management zones, based on soil type, slope position and land use history, and the sampling density was established as one sampling point per one hundred hectares, while for environments smaller than 500 ha minimum of five points must be used. These points are georeferenced and will be revisited for annual monitoring of sustainable soil management, and every five years for soil sampling for SOC, texture, bulk density, pH, electric conductivity (if indicated), and available phosphorus determinations. The monitoring of sustainable soil management will be carried out through a visual evaluation of 12 soil quality parameters, as described in the handbook published by the AGSUS group. The data obtained from the visual evaluation and the soil analyses (bulk density, particle size fractions, C content, and pH) in the baseline monitoring of Argentinean and Brazilian farms during 2022 were analyzed for the relation between visual evaluation score and the means of these soil parameters. The organic matter indicator (OMI)was calculated by the formula OMI = OM/clay plus silt*100. The data base contained visual soil evaluation scores at 80 georeferenced sampling points, representing 12 farms located in different agroecological zones of the Argentinean Pampas, and 47 sampling points on two farms in Mato Grosso, Brazil. Our results showed a relationship between the VE (Visual Evaluation) score and SOC contents of the soils, especially when these were expressed in relation to their fine mineral particles as with the OMI for the soils of the Argentinean Pampa and the Brazilian Mato Grosso. The OMI showed differences between the three VE scores ranging from 4.7 to 6.7 and from 3.1 to 5.1 in the 0–0.1 m and 0.1–0.2 m depths, respectively. Relationships between the VE score and SOC, OMI, Sand, Silt and Clay plus Silt were only found for the 39 cases of VE “moderate” score in Pampas soils, whereas for the 39 cases of “good” scores no significant relations were encountered. These soils had high SOC and OMI, indicating that they are healthy soils, near saturation level, with low C sequestration potential.